PREFERABLE TYPE OF ABSTRACT IN LEADING SCIENTIFIC JOURNALS - L. Doncheva (Trakia Journal of Sciences)
An abstract is perhaps the most important single paragraph in a manuscript since it is used for reference purposes in different scientific databases. There are three major scientific writing styles (APA Style, Chicago Style, Harvard Style) providing different guidelines for creating an abstract. Purpose: The aim of this research was to find out whether there was some dependence between the category of the journals, the country of origin, and the coverage (number of years of publication) and the type of abstracts submitted. Methods: We carried out our investigation through synthesis of data retrieved from scimagojr.com and made an analysis based on the top world-famous 50 sports journals with the highest impact factor for 2018. Results: There were no statistically significant differences and correlations between the researched parameters (type of abstract and the category of journals: 2=1.94; =0.47; C=0.17; type of abstract and the country of origin: 2=3.16; =0.53; C=0.24; type of abstract and coverage: 2=1.81; =0.61; C=0.19). Conclusions: We can assume that there are no obvious criteria for adopting a particular scientific writing style and each journal has their own traditions and favored approach. However, certain differences were outlined.